Training techniques used in training horses (Equus caballus) - Bornhede, Maria (2010)
Instrumental conditioning, the use of reinforcement and punishment, is used when training horses and these procedures may have different consequences regarding animal welfare. The aim of this study was to investigate what kind of reinforcers that are used in training horses and when these reinforcers are used. This study has its focus on positive reinforcement and its advantages and disadvantages. Interviews of five A-level and B -level equestrian coaches about their training methods were conducted to complement the literature search and give a greater understanding to why certain methods are used or not in training horses.